Mineral Rights Cadastre : Promoting Transparent Access to Mineral Resources - Ortega Girones, Enrique; Pugachevsky, Alexandra; Walser, Gotthard (World Bank, Washington, DC, 2014)
This document proposes a set of generally applicable recommendations and good practices for creating a Mineral Rights Cadastre (MRC), an administrative body responsible for overseeing the process of granting and managing mineral licenses throughout a country. The document reviews lessons learned from World Bank-funded projects aimed at reforming mineral rights management and assesses the impacts and benefits of the implemented changes. The document focuses on the MRC system as a key regulatory agency of mining sector administration. This study is also intended to fill a gap in the literature on mining sector administration, as few publications since roughly the 1930s have been dedicated to the overall analysis of MRCs, particularly in relation to modern and recent mining cadastral practices. While the overall concepts and principles presented in this document are intended to be universally valid and applicable, there is no single solution to mining sector development, and it would be unrealistic to believe that actions that have been successful in one country can be directly transferred to others. The MRC of any given country will need to be adapted to that particular country's culture, tradition, existing legal framework, development capacity, and other factors. This document describes the trade-offs that may be necessary to arrive at an acceptable solution; using case studies, it also highlights concrete applications that can be recommended, based on typical country circumstances.